Alternative Methods of Accounting for Long-Term Nonsubsidiary Intercorporate Investments in Common Stock. - O'Connor, Melvin C.; Hamre, James C. (The Accounting Review, 1972)
Abstract This article presents information on evaluating alternative methods of accounting for long-term nonsubsidiary holdings of common stock. Long-term investments by one corporation (investor) in the common stock of another corporation (investee) can be classified in one of two basic categories according to the percentage of the common stock of the investee corporation held by the investor corporation. Holdings of more than 50 percent are classified as subsidiary holdings while holdings of 50 percent or less are classified as nonsubsidiary holdings. Under the cost method, "periodic investor income" consists of dividends received by the investor which are distributed from the investor's proportionate share of undistributed investee earnings accumulated since the acquisition of the investment. The book value of the investment on the investor's books, hereafter referred to as "investment carrying value," is periodically reduced by any dividends received in which distributions in excess of investee earnings since acquisition of the investment. Such dividends are referred to in this paper as "excess dividends." Finally, Opinion 18 states that a senes of operating losses of an investee or other factors may indicate that a decrease in value of the investment has occurred which is other than temporary and should accordingly be recognized.